2013
DOI: 10.1002/app.39096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the filler structure of carbon nanomaterials on the electrical, thermal, and rheological properties of epoxy composites

Abstract: Carbon nanotubes (CNTs) and graphene nanosheets (GNSs) were used as fillers in epoxy composites with the aim of increasing the electrical and thermal conductivities of the composites. The filling of pristine CNTs produced the highest electrical conductivity (r), whereas a high CNT functionalization and the two-dimensional planar structure of GNSs were promising for improving the thermal conductivity. A combination of CNTs and GNSs exploited the advantages of both. When the CNT fraction was larger than 50 wt %,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The synergetic effect of GNPs and other nanofillers in improving the thermal conductivity of epoxy was also observed in the case of low total nanofiller loadings, i.e. 18 wt% total loading of GNPs and CB nanoparticles [14], 1wt% total loading of GNPs and MWCNTs [13], 2 wt% total loading of GNPs and MWCNTs [25] and ! 40 wt% total loading of GNPs and SWCNTs [4].…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The synergetic effect of GNPs and other nanofillers in improving the thermal conductivity of epoxy was also observed in the case of low total nanofiller loadings, i.e. 18 wt% total loading of GNPs and CB nanoparticles [14], 1wt% total loading of GNPs and MWCNTs [13], 2 wt% total loading of GNPs and MWCNTs [25] and ! 40 wt% total loading of GNPs and SWCNTs [4].…”
mentioning
confidence: 76%
“…The addition of 0-D CB nanoparticles helped to increase the thermal conductivity of GNP/epoxy composites by improving the dispersion of GNPs, preventing the settling of GNPs and bridging the gaps among 2-D GNPs [14]. Long and tortuous 1-D CNTs were used to bridge adjacent 2-D GNPs as well as inhibit the aggregation of GNPs, resulting in a high contact area between GNP/CNT structures and epoxy matrix and thus a more efficient percolating nanofiller network with significantly reduced thermal interface resistances, consequently the thermal conductivity of epoxy filled with a mixture of GNPs and CNTs surpassed that of epoxy filled with pure GNPs or CNTs [4,13,25]. However, a further increase of thermal conductivity of epoxy by increasing the total nanofiller loading is hard to realize due to the increased filler aggregation and interfacial thermal resistance as well as dramatically increased viscosity.…”
mentioning
confidence: 99%
“…CNT's electrical conductivity-filled epoxy nanocomposites, with less than 0.5 wt % of CNTs, were improved by several orders of magnitude (Jiang et al 2013a, b;Russ et al 2013;Prolongo et al 2013, He et al 2013Safdari and Al-Haik 2013). Furthermore, thermal conductivity of epoxy matrix at room temperature increased by 300 % on 3 wt% SWCNTs loading, and an additional increase of 10 % once they are magnetically aligned (Li et al 2013a, b, c, d, e).…”
Section: Cnts: In Thermoset Polymeric Compositesmentioning
confidence: 93%
“…Some studies focused on the electrical conductivity properties of CNT-filled epoxy nanocomposites with respect to the aspect ratio and percolation threshold of CNTs. It is found that there is an eight times decrease in the threshold concentration in MWCNT-filled epoxy composites as its length increased from 1 to 50 µm (He et al 2013). Meanwhile, the minimum percolation threshold concentration of MWCNT-filled epoxy was recorded at 0.0021 wt% of MWCNTs (Safdari and Al-Haik 2013).…”
Section: Cnts: In Thermoset Polymeric Compositesmentioning
confidence: 97%
See 1 more Smart Citation